Volume control strategy and patient survival in sepsis-associated acute kidney injury receiving continuous renal replacement therapy: a randomized controlled trial with secondary analysis - Cheol Ho Park; Hee Byung Koh; Jin Hyeog Lee; Hui-Yun Jung; Joohyung Ha; Hyung Woo Kim; Jung Tak Park; Seung Hyeok Han; Shin-Wook Kang; Tae-Hyun Yoo (Scientific Reports, 2024)
Abstract Optimal strategy for volume control and the clinical implication of achieved volume control are unknown in patients with sepsis-associated acute kidney injury (AKI) receiving continuous renal replacement therapy (CRRT). This randomized controlled trial aimed to compare the survival according to conventional or bioelectrical impedance analysis (BIA)-guided volume control strategy in patients with sepsis-associated AKI receiving CRRT. We also compared patient survival according to achieved volume accumulation rate ([cumulative fluid balance during 3 days × 100]/fluid overload measured by BIA at enrollment) as a post-hoc analysis. We randomly assigned patients to conventional volume control strategy (n = 39) or to BIA-guided volume control strategy (n = 34). There were no differences in 28-day mortality (HR, 1.19; 95% CI, 0.63–2.23) or 90-day mortality (HR, 0.99; 95% CI 0.57–1.75) between conventional and BIA-guided volume control group. In the secondary analysis, achieved volume accumulation rate was significantly associated with patient survival. Compared with the achieved volume accumulation rate of ≤  − 50%, the HRs (95% CIs) for the risk of 90-day mortality were 1.21 (0.29–5.01), 0.55 (0.12–2.48), and 7.18 (1.58–32.51) in that of  − 50–0%, 1–50%, and > 50%, respectively. Hence, BIA-guided volume control in patients with sepsis-associated AKI receiving CRRT did not improve patient outcomes. In the secondary analysis, achieved volume accumulation rate was associated with patient survival.